1996
DOI: 10.1023/a:1018484323210
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Prostate cancer frequently metastasizes to bone, and we propose that this process may be facilitated by the adhesion of metastatic cells to bone-derived type I collagen. We examined collagen receptor function and regulation in osteotropic PC-3 human prostatic carcinoma cells. PC-3 cell adhesion to immobilized human type I collagen was promoted by Mn2+ and Mg2+ ions and was RGD-independent. Antibodies directed against beta1 or alpha2 integrin subunits inhibited adhesion to collagen by 90% and 53%, respectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…Given that TGFbdependent effects upon cell adhesion required long exposure times (i.e., longer than 6 h), it is likely that changes in gene expression are necessary. This is supported by prior studies demonstrating that TGFb modulates expression of genes in various cell types associated with adhesion and motility, including: integrins, collagen, and PAI-1 (Ignotz and Massague, 1986;1987;Laiho and Keski-Oja, 1992;Kostenuik et al, 1997;Festuccia et al, 1999). It is also supported by the current study, where TGFb action upon cell adhesion required activation of Smads, which are known transcription factors.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Given that TGFbdependent effects upon cell adhesion required long exposure times (i.e., longer than 6 h), it is likely that changes in gene expression are necessary. This is supported by prior studies demonstrating that TGFb modulates expression of genes in various cell types associated with adhesion and motility, including: integrins, collagen, and PAI-1 (Ignotz and Massague, 1986;1987;Laiho and Keski-Oja, 1992;Kostenuik et al, 1997;Festuccia et al, 1999). It is also supported by the current study, where TGFb action upon cell adhesion required activation of Smads, which are known transcription factors.…”
Section: Discussionsupporting
confidence: 89%
“…We focused investigations upon human prostate because TGFb plays key regulatory roles in this cell type, and because dysregulation of TGFb signaling has been linked to human prostate cancer 1996a, b;Sehgal et al, 1996). We (Rohlff et al, 1998;Liu et al, 2002) and others (Hsing et al, 1996;Kostenuik et al, 1997;Wilding et al, 1989;Festuccia et al, 1999) have shown that TGFb is an important regulator of both cell growth, as well as adhesion and motility, in human prostate. Differential responsiveness to TGFb has been reported in metastatic versus primary prostate cells (Sehgal et al, 1996), while loss of TGFb receptor accompanies progression of human prostate cancer (Kim et al, 1996a).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…To assess the specificity of TGF-β-mediated upregulation of integrin β3 as compared to other related integrin subunits, we evaluated how TGF-β alters expression of integrin αv, as well as a subfamily of β-integrin subunits that can also heterodimerize with integrin αv (integrin subunits β1, β5, β6 and β8). In addition, we evaluated integrin αIIb (glycoprotein-IIb), which is largely restricted to platelets and megakaryocyte-lineage cells but can also heterodimerize with integrin β3 (16), and integrin α2, which facilitates adhesion to type I collagen and is upregulated on prostate cancer lines in response to TGF-β (38). …”
Section: Resultsmentioning
confidence: 99%